Implementasi Moderasi Beragam pada Madrasah Tsanawiyah Al-Khairat Kwandangg Kabupaten Gorontalo Utara - Imas Baguna (Jurnal Manajemen dan Pendidikan Agama Islam, 2023)
Religious moderation plays a crucial role in Indonesia, a society with diverse beliefs and religious backgrounds. Religious leaders, with government support, strive to prevent violence and intolerance in Indonesia. One approach used is interfaith moderation. The concept of moderate Islam becomes a significant religious perspective in addressing diversity in Indonesia. To strengthen the role of Islamic schools (madrasah) in combating radicalism and extremism, religious moderation needs to be incorporated into the madrasah curriculum. The aim of this approach is to mediate between two extreme poles while emphasizing the importance of internalizing religious teachings on one side and understanding the context of religious texts on the other side. To examine this issue, the research was conducted using qualitative methods, particularly a case study. This method aims to find meaning, investigate processes, and gain in-depth understanding of individuals, groups, or situations. In analyzing the data, the researcher applied an interactive model. Data analysis activities include data reduction, data presentation, conclusion drawing, and verification. The research results indicate that religious moderation instilled in students at Madrasah Tsanawiyah Al-Khairat Kwandang, North Gorontalo Regency, not only occurs in formal settings but is also integrated into every learning session. One form of moderation practiced by students is providing advice to fellow students, fostering a sense of care among them.